2004
DOI: 10.1002/rmv.441
|View full text |Cite
|
Sign up to set email alerts
|

Latent and lytic Epstein‐Barr virus replication strategies

Abstract: The Epstein-Barr virus (EBV) can choose between two alternative lifestyles; latent or lytic replication. In the latent state, the EBV genomic DNA, which exists as a closed circular plasmid, appears to behave just like host chromosomal DNA and it has been demonstrated recently that replication of OriP-containing plasmids is indeed dependent on the chromosomal initiation factors, ORC2 and Cdt1. On the other hand, in the viral productive cycle, the EBV genome is amplified 100- to 1000-fold by the viral replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
202
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(207 citation statements)
references
References 82 publications
3
202
0
2
Order By: Relevance
“…The results from this study showed that the levels of p53, p21 WAF-1/CIP-1 and p27 KIP-1 were unchanged before and after induction of the lytic program, whereas elevation of cyclin E/A expression and accumulation of hyperphosphorylated Rb protein were observed. 91 Zta expression in HeLa cells markedly reduced the expression of the cyclin B1 both at RNA and protein levels, indicating that Zta induced a G 2 block in HeLa cells by decreasing the level of cyclin B1. 92 It appeared that the effect of Zta expression on cell cycle progression could occur in different phases of the cell cycle (either G 0 /G 1 or G 2 /M) in a cell type dependent manner.…”
Section: Zta As a Target Of Anticancer Therapymentioning
confidence: 92%
“…The results from this study showed that the levels of p53, p21 WAF-1/CIP-1 and p27 KIP-1 were unchanged before and after induction of the lytic program, whereas elevation of cyclin E/A expression and accumulation of hyperphosphorylated Rb protein were observed. 91 Zta expression in HeLa cells markedly reduced the expression of the cyclin B1 both at RNA and protein levels, indicating that Zta induced a G 2 block in HeLa cells by decreasing the level of cyclin B1. 92 It appeared that the effect of Zta expression on cell cycle progression could occur in different phases of the cell cycle (either G 0 /G 1 or G 2 /M) in a cell type dependent manner.…”
Section: Zta As a Target Of Anticancer Therapymentioning
confidence: 92%
“…1A). Additionally, the constructed CNE1-LMP1 cell line that constitutively expressed LMP1 exhibited markedly increased expression levels of the EBV lytic proteins BZLF1 and BMRF1 (37,38) when compared with the CNE1 control cells (Fig. 1B).…”
Section: Lmp1 Enhances the Expression Levels Of Ebv Lytic Proteins Inmentioning
confidence: 96%
“…Upon reactivation, the EBV immediate-early gene BZLF1 (encoding the protein Zta), the master regulatory lytic gene, is the very first viral lytic gene expressed (Rickinson and Kieff, 2007). It encodes transcription factors that induce an ordered cascade of early and late lytic EBV genes expressions (Tsurumi et al, 2005). Notably, in cell lines infected with latent EBV, the virus can be induced to lytic infection by stimuli such as anti-immunoglobulin (Ig), transforming growth factor-b (TGFb), 12-O-tetradecanoylphorbol-13-acetate or sodium butyrate (SB) (Tovey et al, 1978;zur Hausen et al, 1978;Luka et al, 1979;Takada, 1984;di Renzo et al, 1994).…”
Section: Introductionmentioning
confidence: 99%